Innovation in Language and Culture Preservation Through the Development of a Trilingual Digital Dictionary: Batak Toba – Indonesian – English - Orli Binta Tumanggor; Winda Syafitri; Suci Khairani; Lamtiur Sinambela (FOSTER: Journal of English Language Teaching, 2025)
Language is a vital part of human culture and reflects the identity of a community. Over time, many regional languages face extinction due to a decline in native speakers. One such language is Batak Toba. Its use is decreasing among younger generations because of factors like migration, inter-ethnic marriages, and the growing dominance of Indonesian and foreign languages. If this trend continues, Batak Toba may disappear in the coming generations. This study aims to preserve the Batak Toba language and culture by developing a Trilingual Digital Dictionary (Batak Toba – Indonesian – English). The development follows the 4-D model, which includes defining, designing, developing, and disseminating. The dictionary is evaluated based on its validity, practicality, and effectiveness. The research starts with several analyses: front-end, student, language, task, concept, and goal setting. Then, research instruments are created, media and formats are selected, and an initial prototype is developed. This first version is validated by experts, revised, and tested in classroom settings. Data from these evaluations are analyzed to determine whether the product meets quality standards. The result is a final version of the digital dictionary that is proven to be valid, practical, and effective for language preservation.